Opposite effects of a high-fat diet and calorie restriction on ciliary neurotrophic factor signaling in the mouse hypothalamus - Severi, Ilenia; Perugini, Jessica; Mondini, Eleonora; Smorlesi, Arianna; Frontini, Andrea; Cinti, Saverio; Giordano, Antonio (Frontiers in Neuroscience, 2013)
In the mouse hypothalamus, ciliary neurotrophic factor (CNTF) is mainly expressed by ependymal cells and tanycytes of the ependymal layer covering the third ventricle. Since exogenously administered CNTF causes reduced food intake and weight loss, we tested whether endogenous CNTF might be involved in energy balance regulation. We thus evaluated CNTF production and responsiveness in the hypothalamus of mice fed a high-fat diet (HFD), of ob/ob obese mice, and of mice fed a calorie restriction (CR) regimen. RT-PCR showed that CNTF mRNA increased significantly in HFD mice and decreased significantly in CR animals. Western blotting confirmed that CNTF expression was higher in HFD mice and reduced in CR mice, but high interindividual variability blunted the significance of these differences. By immunohistochemistry, hypothalamic tuberal and mammillary region tanycytes stained strongly for CNTF in HFD mice, whereas CR mice exhibited markedly reduced staining. RT-PCR and Western blotting disclosed that changes in CNTF expression were paralleled by changes in the expression of its specific receptor, CNTF receptor α (CNTFRα). Injection of recombinant CNTF and detection of phospho-signal transducer and activator of transcription 3 (P-STAT3) showed that CNTF responsiveness by the ependymal layer, mainly by tanycytes, was higher in HFD than CR mice. In addition, in HFD mice CNTF administration induced distinctive STAT3 signalling in a large neuron population located in the dorsomedial and ventromedial nuclei, perifornical area and mammillary body. The hypothalamic expression of CNTF and CNTFRα did not change in the hyperphagic, leptin-deficient ob/ob obese mice; accordingly, P-STAT3 immunoreactivity in CNTF-treated ob/ob mice was confined to ependymal layer and arcuate neurons. Collectively, these data suggest that hypothalamic CNTF is involved in controlling the energy balance and that CNTF signalling plays a role in HFD obese mice at specific sites.